The role of implicit beliefs about emotions and emotion regulation on psychological adjustment: a study among youth athletes - Cunha, Miguel; Sofia, Rui; Dias, Claudia (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. Youth psychological health and well-being are currently alarming. Young athletes face the same stressors as their non-athletic peers, in addition to unique challenges related to sports. This study aimed to understand the role of self-control and emotion regulation on the young athlete’s psychological well-being, while also considering the influence of implicit beliefs about emotions.Methods. One-hundred and forty-five athletes ranging from 15 to 21 (16.21 ± 1.44) completed an online survey with self-report measures of trait anxiety, perceived stress, positive and negative affect, subjective happiness, life satisfaction, implicit beliefs about emotions, self-control, and emotion regulation.Results. Findings suggested that implicit beliefs about emotions and self-control predicted better psychological adjustment, whereas expressive suppression was associated with poorer outcomes. However, self-control and emotional regulation were mediators of the relationship between implicit beliefs and psychological adjustment.Conclusions. Incremental beliefs about emotions are central to promoting the young athlete’s psychological adjustment and well-being.
Keywords: self-control; young athletes; emotion regulation; psychological adjustment; implicit beliefs